Advances in hospitality and leisure. Vol. 7 - Chen, Joseph S. (Advances in hospitality and leisure,, 2011)
Advances in Hospitality and Leisure (AHL), a peer-review series published annually, is seeking to deliver refreshing insights from a host of scientific investigations pertaining to hospitality, leisure, and tourism while rendering an academic forum to stimulate discussion on current literature, contemporary issues and emerging trends essential to theory advancement as well as professional practices from a global perspective. The main focus of this series is to divulge the innovative methods of inquiry so as to inspire new research topics that are vital and have been in large neglected. AHL strives to address the needs of the populace willing to disseminate seminal ideas, concepts, and theories derived from scholarly inquiries. Potential readers may retrieve useful texts helping outline new research agendas, suggest viable topics for a dissertation work, and augment the knowledge of the new subjects of learning.